2016
DOI: 10.1370/afm.1994
|View full text |Cite
|
Sign up to set email alerts
|

Discussing Opioid Risks With Patients to Reduce Misuse and Abuse: Evidence From 2 Surveys

Abstract: We used 2 population-representative surveys to evaluate the recommendation from recent clinical guidelines for prescribing opioid analgesics that physicians discuss the risk of long-term use disorders with patients. In nationally representative data we observed a 60% lower rate, after adjustment for covariates, in a self-reported saving of pills among respondents who say they talked with their physicians about the risks of prescription painkiller addiction (67% lower rate without adjustment). These findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 8 publications
0
21
1
Order By: Relevance
“…This highlights the need for more effective training of medical practitioners in pain management and counselling patients regarding the use of prescription analgesics. Additionally, widespread patient education programs informing patients about the potential risks of pharmacotherapy, particularly opioids, should be provided and may have positive behavioural consequences that can lower the risk of addiction and abuse related to prescription medications[ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the need for more effective training of medical practitioners in pain management and counselling patients regarding the use of prescription analgesics. Additionally, widespread patient education programs informing patients about the potential risks of pharmacotherapy, particularly opioids, should be provided and may have positive behavioural consequences that can lower the risk of addiction and abuse related to prescription medications[ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…30 Recent intervention work demonstrates that patient education efforts (particularly discussing risks of painkiller addiction) may reduce self-reported saving of pills. 31 At the time of our parent survey, our institution did not routinely provide patient education regarding storage and/ or disposal of opioid medications; we are currently instituting a patient education campaign on these important topics as a result of this work.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies included educational pamphlets, 320322 web-based interactive education, 323 and clinician-delivered education. 324,325 All interventions that included knowledge as an outcome demonstrated a significant effect, 320,322,323,325 and many studies observed changes in risky behaviors, such as sharing pills, 320,323 pill storage, 320 saving and disposal of pills, 320,321,323,324 driving, 322 and taking more medication than prescribed. 323…”
Section: Recommendationsmentioning
confidence: 99%